Gallic acid attenuates allergic airway inflammation via suppressed interleukin‐33 and group 2 innate lymphoid cells in ovalbumin‐induced asthma in mice. Issue 11 (7th September 2018) - Wang, Xinhua; Zhao, Hongqing; Ma, Chenhui; Lv, Lei; Feng, Jinping; Han, Shuguang
Abstract : Background: Asthma is an inflammatory disease characterized by airway hyperresponsiveness. Gallic acid is a powerful anti‐inflammatory agent. In this study we aimed to investigate the efficacy of gallic acid in asthma treatment and its mechanisms. Methods: An ovalbumin‐induced asthma mouse model was generated. Pro‐inflammatory cell infiltration and T helper (Th2)–associated cytokine release in the bronchoalveolar lavage fluid (BALF) were analyzed to reflect the severity of asthma in mice. An interleukin‐33 (IL‐33)–induced asthma mouse model was also generated to study the mechanism by which gallic acid could improve asthma. Group 2 lymphoid cells (ILC2s) were identified using flow cytometry. Proteins were detected using Western blotting. Results: Ovalbumin significantly increased the infiltration of pro‐inflammatory cells, including eosinophils, macrophages, lymphocytes, and neutrophils, accompanied by enhanced airway hyperesponsiveness. Gallic acid reduced pro‐inflammatory cell infiltration and improved airway hyperresponsiveness. Meanwhile, gallic acid reduced IL‐5 and IL‐13 levels in BALF and decreased expression of IL‐33 in the lungs. Mechanistically, gallic acid inhibited MyD88 expression and downregulated nuclear factor (NF)‐κB signaling to decrease IL‐33 expression. Conclusions: Gallic acid can mollify ovalbumin‐induced asthma in mice, possibly by inhibiting IL‐33‐mediated ILC2 activation and subsequent Th2 cytokine release via downregulation of the MyD88/NF‐κB signaling pathway. ©2018 ARSAAOA, LLC.